POLYSYLLABIC STRATUM ORDERING ANALYSIS IN SCIENTIFIC TEXT: A MORPHOLOGICAL STUDY - Thomson Radesman Lingga; Asnita Sirait; Humaira Restu Maulidia; Cita Mustika Kusumah (Universitas Widyatama, 2021)
The word formation is largely influenced by derivational affixes. These affixes however have certain level orderings called stratum ordering that lead to the formation of new words hierarchically. The study focuses on the investigation of the possible stratum ordering of derivational morphemes in scientific texts and the analysis of how these stratums form polysyllables derivational words. Qualitative research methodology is applied to this study. The data source of this study was taken from http://ijiemjournal.uns.ac.rs/v11/v11-01.html. This journal concerns Industrial Engineering and Management. The intended data are randomly taken from five journals published on Volume 11 | Issue 1 | March 2020 limited to polysyllables of scientific terms. The data were analyzed using the theory of Francis Katamba proposing that the central to lexical morphology is organized in a series of hierarchical strata and also Spencer (1991) supported by Plag and Baayen (2008). This paper concludes in general that the addition of derivational affixes to scientific terms is hierarchically structured based on the theory, such as the placement of strata 1 affixes closer to the root word, the neutrality of stress placement of strata 2 suffixes, and non-netrality of strata 1 suffixes. However, it is also found some inconsistencies in the placement of derivational suffixes in which the second strata are placed closer to the root. This happens when suffix -able is combined with -ity in availability (adjective to noun) or when suffix -ize is combined with -ion to form verb to noun in parameterization. The most formations found is the use of suffixes -ion, -ity for nouns, -ize for verbs, -ive and -able for adjectives.